The Historical Development and Applications of Simple Groups (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the historical development of simple groups andtheir significance in various areas of mathematics and beyond. We discussthe classification theorem, notable contributors to the theory, and applicationsin fields such as algebra, number theory, geometry, and theoreticalphysics, Computer Science. We also discuss some potential use of Simplegroups in current times.